2018
DOI: 10.1111/bph.14205
|View full text |Cite
|
Sign up to set email alerts
|

PDE5 inhibitors – pharmacology and clinical applications 20 years after sildenafil discovery

Abstract: The discovery of the nitric oxide/cGMP pathway was the basis for our understanding of many normal physiological functions and the pathophysiology of several diseases. Since the discovery and introduction of sildenafil, inhibitors of PDE5 have been the first-line therapy for erectile dysfunction (ED). The success of sildenafil in the treatment of ED stimulated research in the field of PDE5 inhibition and led to many new applications, such as treatment of lower urinary symptoms, and pulmonary arterial hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
157
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 361 publications
(176 citation statements)
references
References 77 publications
1
157
0
8
Order By: Relevance
“…This extract was discarded. A second extraction was performed with 600 mL of diethyl ether to obtain osajin (1), and the other isoflavone pomiferin. The mixture obtained was evaporated at reduced pressure to almost dryness, and then diluted with 500 mL of ethanol.…”
Section: Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…This extract was discarded. A second extraction was performed with 600 mL of diethyl ether to obtain osajin (1), and the other isoflavone pomiferin. The mixture obtained was evaporated at reduced pressure to almost dryness, and then diluted with 500 mL of ethanol.…”
Section: Chemistrymentioning
confidence: 99%
“…The inhibitors of phosphodiesterase 5 (PDE5) are currently used in the clinical practice for the treatment of erectile dysfunction, pulmonary hypertension, and lower urinary symptoms [1], but several other potential therapeutic applications are emerging [1,2]. Scientific literature is particularly prolific for what concerns natural compounds or nature-inspired molecules showing inhibitory activity on PDE5 [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A selective α 1A ‐adrenoceptor antagonist, silodosin, has been widely prescribed for patients with BPH/LUTS, as it suppresses the resistance to urine flow in the proximal urethra . Recently, tadalafil, a PDE5 inhibitor, also has been used for the treatment of BPH/LUTS . The PDE5 inhibitors suppress the PDE5 enzymes in the lower urinary tract, thereby, relaxing the urethral smooth muscle and ameliorating the lower urinary tract obstruction, and are also reported to improve bladder ischemia, and suppress afferent nerve activity, collagen synthesis and fibrosis .…”
Section: Introductionmentioning
confidence: 99%
“…5 The PDE5 inhibitors suppress the PDE5 enzymes in the lower urinary tract, thereby, relaxing the urethral smooth muscle and ameliorating the lower urinary tract obstruction, 5 and are also reported to improve bladder ischemia, and suppress afferent nerve activity, collagen synthesis and fibrosis. 5,6 Furthermore, clinical data showed that silodosin and tadalafil have a protective effect on voiding symptoms and storage symptoms in male patients with BPH/LUTS. 5,7 Vascular risk factors, such as hypertension and hyperlipidemia, are involved in the development of bladder overactivity.…”
mentioning
confidence: 99%